Dingbats Baía Formosa: intersections between type design and social cartography from a university extension project - Falcão, Luiza; Felipe Farias, Juliana (InfoDesign, 2023)
The paper presents the Dingbats Baía Formosa project, a university extension activity proposed by the Design and Geography Departments of the Federal University of Rio Grande do Norte (UFRN). The project proposes to use dingbat fonts as a tool in the participatory social mapping process. The study investigates two hypotheses: a) the use of previously designed symbols can contribute to the dynamics of theoretical-practical workshops to support the development of social maps, and b) the implementation of such symbols as dingbat fonts can facilitate mapping in geographic information systems (GIS) software. The project resulted in the elaboration of five fonts representing the elements of the culture of Baía Formosa/RN. It was found that the production of dingbats can facilitate the development of social maps and their implementation in specialized software.